2015
DOI: 10.1056/nejmoa1504347
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality among Persons with Type 2 Diabetes

Abstract: Mortality among persons with type 2 diabetes, as compared with that in the general population, varied greatly, from substantial excess risks in large patient groups to lower risks of death depending on age, glycemic control, and renal complications. (Funded by the Swedish government and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
576
6
43

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 853 publications
(661 citation statements)
references
References 27 publications
36
576
6
43
Order By: Relevance
“…quadruples cardiovascular risk, compared with the general population (6,7), but also leads to an increased risk of cancer, as shown by some cohort studies (5,8).…”
mentioning
confidence: 88%
“…quadruples cardiovascular risk, compared with the general population (6,7), but also leads to an increased risk of cancer, as shown by some cohort studies (5,8).…”
mentioning
confidence: 88%
“…Both ALD and NAFLD appear to be risk factors for T2DM, and T2DM is a risk factor for more severe liver disease in people with ALD or NAFLD (1)(2)(3)(4)(5)(6). The increased risk of CVD, cancer and mortality among people with type 2 diabetes, compared to people without diabetes, is well known (7)(8)(9). There is evidence of an association between NAFLD and CVD among people with and without diabetes although it is recognised that further information is needed in terms of describing the natural history of NAFLD with regard to both its hepatic and extra-hepatic complications(10; 11), On the basis of existing evidence it appears that more advanced liver disease is associated with higher risk of complications (11; 12).…”
mentioning
confidence: 99%
“…In a recent large study of more than 400,000 type 2 diabetic patients and over 2 million controls in Sweden, Tancredi et al also adopted a matching study design with five controls to one case of type 2 diabetes [24]. They found that the associations of type 2 diabetes with death from any cause and death from cardiovascular causes decreased with increasing age.…”
Section: Discussionmentioning
confidence: 99%